Low-impact specialized pilates is better than low intensity steady state for increasing fitness level - Andriana, Laily Mita; Ashadi, Kunjung; Wijaya, Fransisca Januarumi Marhaendra; Antoni, Muhamad Fauzi (Physical Education and Sports: Studies and Research, 2025)
Background: Elderly individuals with disabilities often face challenges in maintaining physical fitness, highlighting the need for effective and appropriate exercise methods tailored to their limitations. Objectives: This study compares the effectiveness of low-impact specialized Pilates and Low-Intensity Steady-State (LISS) exercise in improving fitness levels among older adults with mild to moderate disabilities. The unique advantage of Pilates in enhancing balance and core strength is presented as a novel contribution. Methods: A quasi-experimental design with pre-test and post-test assessments was employed, involving 40 elderly participants with disabilities divided into two intervention groups over 8 weeks. Participants were selected through purposive sampling based on the inclusion criteria of 60–75 years with mild to moderate disabilities. Fitness levels were assessed using the Senior Fitness Test, which evaluates muscular strength, balance, flexibility, and aerobic capacity. Results: Data analysis was conducted using the Shapiro–Wilk test, paired sample t-test, and independent sample t-test. The results demonstrated that the low-impact specialized Pilates group showed significant improvements in core strength, balance, and flexibility, whereas the LISS group exhibited greater improvements in aerobic capacity. Conclusions: In conclusion, low-impact specialized Pilates is more effective in enhancing overall fitness among elderly individuals with disabilities. Therefore, it is recommended as a suitable exercise modality for rehabilitation and health maintenance programs to improve this population's quality of life and functional independence.